2016
DOI: 10.1364/ao.55.008390
|View full text |Cite
|
Sign up to set email alerts
|

Generation of high-intensity spectral supercontinuum of more than two octaves in a water jet

Abstract: In this paper, we demonstrate experimentally for the first time (to our knowledge) the generation of spectral supercontinuum (SC) of more than two octaves with high intensity in a water jet. The spectrum of the generated SC extends from 350 to 1400 nm, with intensities up to 1011 W/cm2, and its generation efficiency is more than 50%. For the pump intensity 3.0×1012 W/cm2 in the spectral range from 400 to 800 nm, the spectrum is nearly flat (less than 40% deviation), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…These studies demonstrated that a typical SC spectrum covers the 400-1100 nm range [177]. A broader SC spectrum spanning wavelengths from 350 to 1400 nm was reported using a thin water jet instead of a thick cell [180]. In the range of anomalous GVD of water (with laser wavelengths above 1 μm), the SC spectrum with the focusing condition-controllable position of the blue peaks was demonstrated when pumped by the fundamental harmonics of the Nd:glass laser (1055 nm) [91].…”
Section: Watermentioning
confidence: 84%
See 1 more Smart Citation
“…These studies demonstrated that a typical SC spectrum covers the 400-1100 nm range [177]. A broader SC spectrum spanning wavelengths from 350 to 1400 nm was reported using a thin water jet instead of a thick cell [180]. In the range of anomalous GVD of water (with laser wavelengths above 1 μm), the SC spectrum with the focusing condition-controllable position of the blue peaks was demonstrated when pumped by the fundamental harmonics of the Nd:glass laser (1055 nm) [91].…”
Section: Watermentioning
confidence: 84%
“…These studies demonstrated that a typical SC spectrum covers the 400 − 1100 nm range 177 . A broader SC spectrum spanning wavelengths from 350 nm to 1400 nm was reported using a thin water jet instead of a thick cell 180 .…”
Section: B Watermentioning
confidence: 94%
“…SC has a wide range of applications, such as time-resolved excitation and absorption spectroscopy [45], optical pulse compression [46] and the characterization of laser-induced structural transitions [47], etc. The SC generation induced by femtosecond laser in water has been extensively studied in the past few decades, both experimentally and theoretically [39,[48][49][50][51][52][53][54][55][56]. Quite a few approaches are used to study the property of the SC and to control the SC generation [39,[48][49][50][51][52][53][54][55][56].…”
Section: Femtosecond Laser Filamentation and Sc Generation In Watermentioning
confidence: 99%
“…The SC generation induced by femtosecond laser in water has been extensively studied in the past few decades, both experimentally and theoretically [39,[48][49][50][51][52][53][54][55][56]. Quite a few approaches are used to study the property of the SC and to control the SC generation [39,[48][49][50][51][52][53][54][55][56]. For example, the coherence of the SC can be studied by the interference method [39,52].…”
Section: Femtosecond Laser Filamentation and Sc Generation In Watermentioning
confidence: 99%
“…Here E is the radiation electric field, z is the direction of propagation, τ = t − n0 c z is the time in the moving frame of reference, t is time and c is the speed of light in vacuum. The parameters n 0 and a characterize the dispersion of the linear refractive index of the medium n(ω) = n 0 + acω 2 , g is related to the nonlinear refractive index coefficient of the medium as n 2 (ω) = 3gc/2 [23,24], ρ is the concentration of atoms in highly excited states, j is current density, generated by free electrons of the plasma induced by the optical radiation field, coefficients α and β characterize the efficiency of population of highly excited electronic states and free carrier generation in the medium, τ is the effective relaxation time of populations of highly excited states and τ c is the average collisional relaxation time of the free electrons in the generated plasma.…”
Section: Intense Ultrashort Optical Pulse Field Dynamics In the Self-...mentioning
confidence: 99%